A single-crystal lithium-rich manganese-based cathode material based on eutectic molten salt and a preparation method thereof

CN122959853APending Publication Date: 2026-10-23杭州市实业投资集团有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611202813.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

现有的单晶制备方法通常需要极高的煅烧温度,不仅增加了能耗,且容易导致锂元素的高温挥发和材料结构的破坏

Benefits of technology

本发明提供的方法具备以下有益效果:本发明引入氟化锂、氟化钾和氟化钠的共晶熔盐体系,利用共晶体系的低熔点特性,在煅烧阶段为富锂锰基前驱体提供了均匀的液相生长环境。液相环境加速了原子的扩散速率,降低了单晶化所需的表面能,促使多晶颗粒融合成结晶度高、形貌规则的单晶颗粒,减少了材料内部的晶界,从而抑制了电池循环过程中的晶界副反应与微裂纹生成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959853A_ABST
    Figure CN122959853A_ABST
Patent Text Reader

Abstract

The application discloses a single-crystal lithium-rich manganese-based positive electrode material based on a eutectic molten salt and a preparation method thereof, and belongs to the technical field of lithium ion battery positive electrode materials. The preparation method comprises the following steps: preparing a polycrystal lithium-rich manganese-based oxide precursor; mixing the precursor with a eutectic molten salt composed of at least two of lithium fluoride, potassium fluoride and sodium fluoride in proportion; and performing high-temperature calcination treatment on the mixture, and then performing washing and drying to obtain the single-crystal lithium-rich manganese-based positive electrode material. The eutectic fluoride molten salt system is introduced, and the low eutectic point characteristic is utilized to provide a uniform liquid growth medium for the precursor in the calcination stage, so that the polycrystal particles are recrystallized to develop into a single-crystal structure with regular morphology and no internal grain boundary. The single-crystal structure effectively cuts off the corrosion path of the electrolyte along the grain boundary, inhibits the interface side reaction and the generation of particle microcracks in the cycle process, and thus improves the high-voltage structural stability and cycle capacity retention rate of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode material technology, specifically to a single-crystal lithium-rich manganese-based cathode material based on eutectic molten salt and its preparation method. Background Technology

[0002] Lithium-rich manganese-based cathode materials are promising next-generation energy density power battery cathode materials due to their high theoretical specific capacity. However, polycrystalline lithium-rich manganese-based materials prepared by conventional solid-state methods suffer from grain boundary side reactions during cycling, leading to voltage decay and limited cycle stability.

[0003] Single crystallization is a way to solve the aforementioned structural instability problems. Single crystal particles lack grain boundaries, which can suppress electrolyte penetration and side reactions, improving the structural stability and cycle life of the material. Existing single crystal preparation methods typically require extremely high calcination temperatures, which not only increases energy consumption but also easily leads to high-temperature volatilization of lithium and damage to the material structure. Therefore, it is necessary to develop a preparation method that can promote single crystal growth at a relatively mild temperature. Summary of the Invention

[0004] This invention provides a single-crystal lithium-rich manganese-based cathode material based on eutectic molten salt and its preparation method. By utilizing a eutectic fluoride molten salt system with a specific ratio, the melting point of the reaction system is reduced, a liquid phase growth environment is provided, and the primary particles of the lithium-rich manganese-based material are promoted to develop into a single-crystal structure with a regular morphology, thereby improving the electrochemical performance of the material.

[0005] The first aspect of this invention discloses a method for preparing a single-crystal lithium-rich manganese-based cathode material based on eutectic molten salt, comprising the following steps: S1. Preparation of polycrystalline lithium-rich manganese-based oxide precursors; S2. The polycrystalline lithium-rich manganese-based oxide precursor is mixed with a eutectic molten salt to obtain a mixture, wherein the eutectic molten salt is composed of at least two selected from lithium fluoride, potassium fluoride and sodium fluoride; S3. The mixture is calcined, then washed and dried to obtain a single-crystal lithium-rich manganese-based cathode material based on eutectic molten salt.

[0006] Preferably, in step S2, the mass ratio of the polycrystalline lithium-rich manganese-based oxide precursor to the eutectic molten salt is 1:2 to 1:10.

[0007] Preferably, the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride.

[0008] Preferably, in the eutectic molten salt, the molar ratio of lithium fluoride, potassium fluoride and sodium fluoride is (3-5):(1-3):(3-5).

[0009] Preferably, step S1 specifically includes the following steps: S11. Dissolving a lithium source, a nickel source, a manganese source and a complexing agent in deionized water to form a mixed solution; S12. Pre-sintering the mixed solution to obtain the polycrystalline lithium-rich manganese-based oxide precursor.

[0010] Preferably, the lithium source is lithium acetate dihydrate, the nickel source is nickel acetate tetrahydrate, the manganese source is manganese acetate tetrahydrate, and the complexing agent is citric acid monohydrate.

[0011] Preferably, the molar ratio of lithium acetate dihydrate, nickel acetate tetrahydrate, and manganese acetate tetrahydrate is (6.18-6.60):1:3, the molar ratio of citric acid monohydrate to the total molar amounts of lithium acetate dihydrate, nickel acetate tetrahydrate, and manganese acetate tetrahydrate is (0.8-1.2):1, and the lithium acetate dihydrate is in molar excess of 3% to 10% relative to the theoretical stoichiometry of the target product.

[0012] Preferably, the pre-sintering step in S12 includes: heating to 400°C to 600°C at a rate of 1°C / min to 5°C / min in an air atmosphere and holding at that temperature for 2h to 5h, followed by heating to 800°C to 1000°C at a rate of 1°C / min to 3°C / min and holding at that temperature for 8h to 15h.

[0013] Preferably, the calcination treatment in S3 specifically involves heating to 800°C to 1000°C at a rate of 1°C / min to 5°C / min and holding at that temperature for 8 hours to 15 hours.

[0014] The second aspect of this invention discloses a single-crystal lithium-rich manganese-based cathode material, prepared by any of the preparation methods described above, wherein its chemical composition satisfies the formula... .

[0015] Beneficial effects The method provided by this invention has the following beneficial effects: This invention introduces a eutectic molten salt system of lithium fluoride, potassium fluoride, and sodium fluoride. Utilizing the low melting point of the eutectic system, a uniform liquid-phase growth environment is provided for the lithium-rich manganese-based precursor during the calcination stage. The liquid-phase environment accelerates the atomic diffusion rate, reduces the surface energy required for single crystallization, and promotes the fusion of polycrystalline particles into highly crystalline, regularly shaped single crystal particles. This reduces grain boundaries within the material, thereby suppressing grain boundary side reactions and microcrack formation during battery cycling. Attached Figure Description

[0016] Figure 1 This is a morphology diagram of the product after calcination of the mixed eutectic molten salt in Example 1. Detailed Implementation

[0017] Example 1 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0018] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0019] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0020] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0021] Example 2 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0022] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0023] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 2.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0024] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0025] Example 3 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0026] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0027] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 10.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0028] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0029] Example 4 S11. Dissolve 19.10 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.18:1:3, i.e., the lithium source is in 3% molar excess relative to the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0030] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0031] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0032] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0033] Example 5 S11. Dissolve 20.40 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.60:1:3, meaning the lithium source is 10% molarly in excess of the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0034] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0035] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0036] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0037] Example 6 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0038] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0039] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 3:1:3. Mechanically grind for 0.5 h to obtain a mixture.

[0040] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0041] Example 7 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0042] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0043] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 5:3:5. Mechanically grind for 0.5 h to obtain a mixture.

[0044] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0045] Example 8 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0046] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0047] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0048] S3. The mixture was heated to 800°C at a rate of 2°C / min in air and held at that temperature for 15 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0049] Example 9 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 63.36 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is approximately 0.96:1) and stir to form a stable complex solution.

[0050] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0051] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0052] S3. The mixture was heated to 1000℃ in air at a rate of 2℃ / min and held at that temperature for 8 hours. After cooling, it was washed with water and centrifuged (8000r / min) until no fluoride / chloride ions were detected. Then it was dried at 80℃ to obtain a single-crystal lithium-rich manganese-based cathode material.

[0053] Example 10 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 52.77 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is 0.8:1) and stir to form a stable complex solution.

[0054] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0055] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0056] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0057] Example 11 S11. Dissolve 19.66 g of lithium acetate dihydrate, 7.54 g of nickel acetate tetrahydrate, and 22.28 g of manganese acetate tetrahydrate in 1 L of deionized water to form a mixed solution (at this point, the molar ratio of Li:Ni:Mn is 6.36:1:3, meaning the lithium source is in 6% molar excess relative to the theoretical product). Add 79.16 g of citric acid monohydrate (the molar ratio of citric acid monohydrate to the total metal is 1.2:1), and stir to form a stable complex solution.

[0058] S12. After concentrating and dehydrating the complex solution, the temperature is increased to 500℃ at a rate of 3℃ / min and held for 3h in air atmosphere, and then increased to 900℃ at a rate of 2℃ / min and held for 10h to obtain a polycrystalline lithium-rich manganese-based oxide precursor.

[0059] S2. Weigh 1.0 g of the polycrystalline lithium-rich manganese-based oxide precursor and mix it with 4.0 g of eutectic molten salt, wherein the eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride in a molar ratio of 4:2:4. Mechanically grind for 0.5 h to obtain a mixture.

[0060] S3. The mixture was heated to 900°C at a rate of 2°C / min in air and held at that temperature for 10 hours. After cooling, it was washed with water and centrifuged (8000 r / min) until no fluoride / chloride ions were detected. Then it was dried at 80°C to obtain a single-crystal lithium-rich manganese-based cathode material.

[0061] The present invention further includes the following comparative examples.

[0062] Comparative Example 1 The preparation method is the same as in Example 1, except that the polycrystalline lithium-rich manganese-based oxide precursor obtained in S1 is not subjected to any subsequent molten salt mixing and secondary reconstruction calcination, and is directly used as the final sample.

[0063] Comparative Example 2 The preparation method is the same as in Example 8, except that in step S2, 100% pure lithium fluoride (LiF) powder of the same purity is used as a single molten salt instead of the ternary eutectic molten salt.

[0064] Comparative Example 3 The preparation method is the same as in Example 1, except that in step S2, 100% pure potassium chloride (KCl) is used instead of ternary eutectic molten salt.

[0065] Comparative Example 4 The preparation method is the same as in Example 1, except that in step S2, the mass ratio of the polycrystalline lithium-rich manganese-based oxide precursor to the eutectic molten salt is adjusted to 1:1.

[0066] Comparative Example 5 The preparation method is the same as in Example 1, except that in step S11, the amount of lithium acetate dihydrate is not overcompensated, so that the molar ratio of Li:Ni:Mn is 6.00:1:3.

[0067] Comparative Example 6 The preparation method is the same as in Example 1, except that in step S3, the calcination temperature is reduced to 700°C and held for 10 hours.

[0068] After completing the preparation of Examples 1-11 and Comparative Examples 1-6, the macroscopic physical characteristics of each group of samples after calcination and cooling were recorded, as shown in Table 1.

[0069] Table 1: Macroscopic physical characteristics of Examples 1-11 and Comparative Examples 1-6 The calcined products of Examples 1-11 all exhibited a dense, blocky structure with crucible adhesion, demonstrating that the ternary eutectic molten salt system defined in this invention, with its low eutectic point, successfully constructed an abundant liquid-phase growth environment at a mild temperature. In contrast, Comparative Example 2 (Comparative Example 8) used pure LiF molten salt. At a calcination temperature of 800°C, the product remained a loose powder and failed to form a liquid phase because it did not reach the inherent melting point of LiF (approximately 845°C). This objectively shows that the eutectic system of this invention, with its low eutectic point, effectively solves the harsh high-temperature conditions required for single crystal growth, and can construct an abundant liquid-phase environment for single crystal growth at a milder temperature.

[0070] For the baseline embodiment and the core comparative example, the positive electrode active material, conductive agent, and polyvinylidene fluoride binder were mixed at a mass ratio of 8:1:1 to prepare the electrode sheet. The coin cells were assembled in an argon-atmospheric glove box. The electrolyte was a 1.0M LiPF6 dissolved in a 1:1 EC:DMC mixed solvent (with 1wt% FEC added). The test temperature was kept constant at 25°C, and the voltage window was 2.0V-4.8V. The test results are summarized in Table 2.

[0071] Table 2: Comparison of Electrochemical Performance Test Results between Examples and Comparative Examples Table 2 further shows that Examples 1-9, reconstructed in this liquid-phase environment, not only exhibited excellent initial coulombic efficiency (approximately 94% to 95.6%), but also maintained a capacity retention rate between 86.7% and 92.3% after 100 charge-discharge cycles at 0.5C. In contrast, Comparative Example 1 (the original polycrystalline sample without molten salt) shows loose, fine fragments without adhesion in Table 1, indicating the absence of a liquid-phase environment; its initial coulombic efficiency in Table 2 is only 88.5%, and its capacity retention rate after 100 cycles is only 71.5%. This correspondence between the macroscopic state and the electrochemical data objectively demonstrates that the liquid-phase reconstruction environment provided by the eutectic molten salt in this application has a direct synergistic effect on improving the interfacial kinetics and cycle stability of the cathode material.

[0072] According to Table 1, Comparative Example 2, using pure LiF as a single molten salt, failed to melt at 800°C, lacking a liquid-phase reconstruction process, and therefore its product failed to achieve single-crystal formation. Corresponding to the electrochemical performance in Table 2, Comparative Example 2's capacity retention after 100 cycles was only 72.6%, similar to the performance of the polycrystalline original sample without molten salt (Comparative Example 1). However, Example 8 (eutectic system) at the same temperature successfully reconstructed the eutectic liquid phase, achieving an initial discharge specific capacity of 225.8 mAh / g, an initial coulombic efficiency of 94.2%, and a capacity retention of 91.1%. This further confirms the excellent effect of the eutectic system of this invention in promoting single-crystal formation and improving the overall electrochemical performance of materials at mild temperatures.

[0073] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a single-crystal lithium-rich manganese-based cathode material based on eutectic molten salt, characterized in that, The process includes the following steps: S1. Preparing a polycrystalline lithium-rich manganese-based oxide precursor; S2. Mixing the polycrystalline lithium-rich manganese-based oxide precursor with a eutectic molten salt to obtain a mixture, wherein the eutectic molten salt is composed of at least two of lithium fluoride, potassium fluoride, and sodium fluoride; S3. Calcining the mixture, followed by washing and drying, to obtain a single-crystal lithium-rich manganese-based cathode material.

2. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of the polycrystalline lithium-rich manganese-based oxide precursor to the eutectic molten salt is 1:2 to 1:

10.

3. The preparation method according to claim 1, characterized in that, The eutectic molten salt is composed of lithium fluoride, potassium fluoride and sodium fluoride.

4. The preparation method according to claim 3, characterized in that, In the eutectic molten salt, the molar ratio of lithium fluoride, potassium fluoride and sodium fluoride is (3-5):(1-3):(3-5).

5. The preparation method according to claim 1, characterized in that, S1 specifically includes the following steps: S11. Dissolving a lithium source, a nickel source, a manganese source and a complexing agent in deionized water to form a mixed solution; S12. Pre-sintering the mixed solution to obtain the polycrystalline lithium-rich manganese-based oxide precursor.

6. The preparation method according to claim 5, characterized in that, The lithium source is lithium acetate dihydrate, the nickel source is nickel acetate tetrahydrate, and the manganese source is manganese acetate tetrahydrate; the complexing agent is citric acid monohydrate.

7. The preparation method according to claim 6, characterized in that, The molar ratio of lithium acetate dihydrate, nickel acetate tetrahydrate, and manganese acetate tetrahydrate is (6.18-6.60):1:3, and the molar ratio of citric acid monohydrate to the total molar amounts of lithium acetate dihydrate, nickel acetate tetrahydrate, and manganese acetate tetrahydrate is (0.8-1.2):

1.

8. The preparation method according to claim 5, characterized in that, The pre-sintering step in S12 includes: heating to 400°C to 600°C at a rate of 1°C / min to 5°C / min in an air atmosphere and holding for 2h to 5h, followed by heating to 800°C to 1000°C at a rate of 1°C / min to 3°C / min and holding for 8h to 15h.

9. The preparation method according to claim 1, characterized in that, The calcination process in S3 specifically involves heating to 800°C to 1000°C at a rate of 1°C / min to 5°C / min, and holding at that temperature for 8 to 15 hours.

10. A single-crystal lithium-rich manganese-based cathode material, characterized in that, The chemical composition of the sample prepared by any one of claims 1 to 9 satisfies the formula... .